Effects of disorder on deformation and failure of brittle porous materials - Ritter, Jonas; Shegufta, Shucheta; Zaiser, Michael (Journal of Statistical Mechanics-Theory and Experiment, 2023)
The mechanical behavior of porous materials depends strongly on porosity and pore geometry, but also on morphological parameters characterizing the spatial arrangement of pores. Here we use bond-based peridynamics to study effects of disorder on the deformation and failure behavior of brittle porous solids both in the quasi-static limit and in case of dynamic loading scenarios. We show that structural disorder, which has a strong influence on stiffness, strength and toughness in the quasi-static limit, becomes less relevant under dynamic loading conditions.
CRIS-Team Scopus Importer:2023-05-19
Keywords: disorder; failure; peridynamics; porous material